Acute traumatic quadrilateral space syndrome following scapula fracture - Mahjoub, Sabri (J Clin Orthop Trauma, 2019)
The acute tunnel syndrome of the quadrilateral space of Velpeau is a very rare entity in which the axillary nerve and the posterior humeral circumflex artery experience brutal compression in shoulder injuries. We report the case of a burst fracture of the right scapula with great displacement of the lateral border occasioning a total isolated paralysis of the right axillary nerve by axillary nerve compression. The lateral scapula border fracture was reduced and stabilized with neurolysis of the axillary nerve through a posterior approach. The recovery of the axillary nerve occurred in ten weeks. Our case is original, not only because of the rarity of isolated axillary nerve injury follwing scapula fractures without shoulder dislocation, but also because the compression of the axillary nerve by bone impingement could be undiagnosed and comprise prognosis.